2019
DOI: 10.1111/nan.12548
|View full text |Cite
|
Sign up to set email alerts
|

Early disease course is unaltered in mucopolysaccharidosis type IIIA (MPS IIIA) mice lacking α‐synuclein

Abstract: 2019)Neuropathology and Applied Neurobiology 45, 715-731 Early disease course is unaltered in mucopolysaccharidosis type IIIA (MPS IIIA) mice lacking a-synuclein Background: Sanfilippo syndrome (mucopolysaccharidosis type IIIA; MPS IIIA) is an inherited paediatric-onset neurodegenerative disorder caused by the lysosomal deficiency of sulphamidase with subsequent accumulation of heparan sulphate. The pathological mechanisms responsible for clinical disease are unknown; however, intraneuronal accumulation of agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…This is in line with a study by Sambri et al which demonstrated that perikaryal accumulation of insoluble α-synuclein and increased proteasomal degradation of cysteine string protein α (CSPα) led to their deficiency in the presynaptic terminal and consequently affected synaptic vesicle integrity and recycling [130]. In contrast, a recent study demonstrated that genetic depletion of α-synuclein failed to rescue or reduce cognitive and motor symptoms in an MPS IIIA mouse model [131]. Autophagic processes in these mice were not improved either, with defective macroautophagy as well as elevated numbers of phosphorylated tau and ubiquitin inclusions similar to those in congenic MPS IIIA mice.…”
Section: Autophagic Defects and Accumulation Of Protein Aggregatessupporting
confidence: 88%
See 1 more Smart Citation
“…This is in line with a study by Sambri et al which demonstrated that perikaryal accumulation of insoluble α-synuclein and increased proteasomal degradation of cysteine string protein α (CSPα) led to their deficiency in the presynaptic terminal and consequently affected synaptic vesicle integrity and recycling [130]. In contrast, a recent study demonstrated that genetic depletion of α-synuclein failed to rescue or reduce cognitive and motor symptoms in an MPS IIIA mouse model [131]. Autophagic processes in these mice were not improved either, with defective macroautophagy as well as elevated numbers of phosphorylated tau and ubiquitin inclusions similar to those in congenic MPS IIIA mice.…”
Section: Autophagic Defects and Accumulation Of Protein Aggregatessupporting
confidence: 88%
“…Autophagic processes in these mice were not improved either, with defective macroautophagy as well as elevated numbers of phosphorylated tau and ubiquitin inclusions similar to those in congenic MPS IIIA mice. Thus, the accumulation of phosphorylated tau is thought to be more relevant to the development of neuropathology [131]. Taken together, these results indicate that aggregate-prone proteins linked to neurodegeneration in adult neurologic disorders such as Alzheimer's and Parkinson's disease accumulate in the MPS III brain, though the specific effects of these proteins (and their interaction) on clinical progression of the disease remain to be clarified.…”
Section: Autophagic Defects and Accumulation Of Protein Aggregatesmentioning
confidence: 95%
“…1 ), concordant with previous studies [ 8 , 16 ] and reflecting human mid-stage disease cognitive skill regression and dementia [ 18 ]. To date, the water crossmaze has not been widely employed as the Morris Water Maze (MWM) has traditionally been used reporting memory and learning impairment in MPS IIIA mice as early as 4 months of age [ 12 , 27 ]. However, Fu et al (2016) [ 7 ] showed 7.5 months was the earliest age of impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Behaviour studies in mice can be variable due to differences in environmental factors and equipment, animal handling and investigator interpretations, mouse housing, upbringing and prior (testing) experience [ 11 ]. For example, hypoactivity has been reported at 3–8 months of age in MPS IIIA mice [ 8 , 12 , 13 ] and hyperactivity [ 14 , 15 ] or “normal” activity has been found at 2–9 months of age [ 9 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dopamine was quantified as per. 36 Briefly, tissues were homogenised and sonicated in 50:50 methanol: water, and 100 μL of homogenate was added to 10 μL of d 4 dopamine internal standard (1000 ng/mL); 400 μL of acetonitrile was added, and samples were vortexed for 1 minute and then cooled at −20 C for 30 minutes. Following centrifugation, the supernatant (~350 μL) was removed into a glass tube and dried down under nitrogen.…”
Section: Dopamine and Glutamate Quantificationmentioning
confidence: 99%